I need to simplify 2 expressions:

a)$\displaystyle \frac{7}{(x-4)(x-4)}$

b)$\displaystyle \frac{-3\sqrt{x-2}}{2(x-2)^2}$

Printable View

- Mar 21st 2009, 03:09 PMBernicesimplify
I need to simplify 2 expressions:

a)$\displaystyle \frac{7}{(x-4)(x-4)}$

b)$\displaystyle \frac{-3\sqrt{x-2}}{2(x-2)^2}$ - Mar 21st 2009, 03:58 PMThe Second Solution
Are you meant to use index laws? If so then note:

a) $\displaystyle \frac{7}{(x-4)(x - 4)} = \frac{7}{(x-4)^2} = 7 (x - 4)^{-2}$ (the last is a debatable simplification).

b) $\displaystyle \sqrt{x - 2} = (x - 2)^{1/2}$. Now use the fact that $\displaystyle \frac{a^{1/2}}{a^2} = a^{\frac{1}{2} - 2} = a^{-3/2} = \frac{1}{a^{3/2}} = \frac{1}{a \sqrt{a}}$.

(Judging from your other posts the algebra here*should*be routine to someone with your background).

**Note:**Simplify is a very vague word to use without a broader context in which to place these question.